A survey of available Abaca products for the interiors - Bernardo, Fe Luz R.
Interior design was an emerging field which concentrated in the design of the interior of a building in accordance to the needs and tastes of the occupants while making the place aesthetically wholesome at the same time. In the Philippines, the concept of the subject came from Western countries. Sad to say, ideas which most of the Filipino Interior Designers used came from the west, too. This was vastly inappropriate since Western countries had a different climate and geological position from the Filipinos. Culture was another thing. Inspite of foreign domination over the years. Filipinos were still able to develop their own traditions and beliefs and most important, their own crafts and art which they could call their very own. But in borrowing Western ideas, these had been extremely taken for granted and in some cases, ignored. Therefore, Filipinos still looked down on themselves without realizing their own uniqueness and ingenuity. In borrowing Interior Design ideas from the west, the designers were not only inadequately satisfying the needs of the Filipinos but they were also using artistic their artistic touch in developing a culture that was from a different land. Filipino culture was therefore coming to a complete stop. It is time that Filipino interior designers stop looking beyond the seas to fulfill the requirements of a Filipino building interior and start wandering around their own backyard instead. This survey was conducted to show an alternative to the usual Western interior finishes like the vinyl wallpaper and floorcover, along with furniture and soft furnishings made of plastic, metal and wood not common in the Philippines. This was a study of a native indigenous material, which was ABACA. This survey was concentrated in the use of Abaca as wallcover, floorcover, soft furnishings and as part of furniture as of the present time. It was done in Metro Manila and one of the leading producers of Abaca products, which was Albay, Bicol, specifically; Legazpi, Old Albay, and Daraga. The researchers found problems such as the uncooperative manner of most companies within the Metro Manila area to assist in the survey. The survey in Albay, Bicol was done with a limited amount of time due to financial constraints.